THE IMPACT OF THE IMPLEMENTATION OF THE LATEST PSAK ON THE QUALITY OF FINANCIAL REPORTS OF PUBLIC COMPANIES IN INDONESIA - Nia Kurniasih; Iin Safariah (RADJA PUBLIKA, 2025)
Changes in accounting regulations through the implementation of the latest Financial Accounting Standards Statements (PSAK) have had a significant impact on the financial reporting practices of public companies in Indonesia. This study aims to analyze the impact of the implementation of the latest PSAK on the quality of issuers' financial reports, by assessing the aspects of relevance, reliability, and comparability of the reports produced. This study uses a quantitative approach with a documentation study method on the annual financial reports of public companies before and after the implementation of new standards, such as PSAK 71, 72, and 73. The analysis was carried out using a regression statistical test to see the relationship between variables. The results of the study indicate that the implementation of the latest PSAK significantly improves the quality of financial reports, especially in terms of transparency and relevance of information. However, challenges were also found in terms of adapting the recording system and increasing the burden of accounting compliance. In conclusion, the implementation of the latest PSAK contributes positively to the quality of issuers' financial reports in Indonesia, but adequate technical assistance is needed for companies to optimize the benefits of implementing these standards.